Genetic Diversity of Olive (Olea europaea L.) Cultivars Assessed by Genotyping-by-Sequencing in Southern Peru - Martín Eloy Casilla García; Rina Alvarez Becerra; José Cotrado Cotrado; Juan Iván Casilla Rondán; Janet Libertad Huatuco Coaquira; Edgar Virgilio Bedoya Justo (Agriculture)
The genetic diversity of the olive tree (Olea europaea L.) is critical for enhancing crop resilience and productivity under changing climatic conditions. Peru’s southern region, particularly Tacna, hosts over 30 olive cultivars, yet their genetic structure remains poorly characterized. This study aimed to evaluate the morphological and genomic diversity of ten economically important olive varieties cultivated in 15 sectors across Tacna and Jorge Basadre provinces. A total of 92 mother plants were selected for morphological assessment using 25 standardized descriptors. Additionally, genomic DNA was extracted from 30 samples and subjected to genotyping-by-sequencing (GBS). Quality metrics confirmed the efficiency of a modified 6h-DNA extraction protocol. Bioinformatic analysis identified hundreds of thousands of SNPs per variety, with a high transition/transversion ratio (∼2.1), indicating reliable variant calls. Phylogenetic clustering revealed three diversity groups, with the olive cultivars Ascolana and Frantoio exhibiting high genetic variability, and Arbequina and Leccino—also olive cultivars—showing reduced diversity. The integration of phenotypic and genomic data highlights hidden variability and supports informed selection and conservation strategies. These findings provide a genomic baseline for breeding programs and genetic resource management in emerging olive-growing regions such as southern Peru.